Pediatric Outcome after Maternal Cancer Diagnosed during Pregnancy - Amant, Frédéric; Vandenbroucke, Tineke; Verheecke, Magali; Fumagalli, Monica; Halaska, Michael J; Boere, Ingrid; Han, Sileny; Gziri, Mina Mhallem; Peccatori, Fedro; Rob, Lukas; Lok, Christianne; Witteveen, Petronella; et al. (The New England journal of medicine, 2015)
BACKGROUND: Data on the long-term outcome of children who are exposed to maternal cancer with or without treatment during pregnancy are lacking. METHODS: In this multicenter case-control study, we compared children whose mothers received a diagnosis of cancer during the pregnancy with matched children of women without a cancer diagnosis. We used a health questionnaire and medical files to collect data regarding neonatal and general health. All children were prospectively assessed (by means of a neurologic examination and the Bayley Scales of Infant Development) at 18 months, 36 months, or both. A cardiac assessment was performed at 36 months. RESULTS: A total of 129 children (median age, 22 months; range, 12 to 42) were included in the group whose mother had cancer (prenatal-exposure group) with a matching number in the control group. During pregnancy, 96 children (74.4%) were exposed to chemotherapy (alone or in combination with other treatments), 11 (8.5%) to radiotherapy (alone or in combination), 13 (10.1%) to surgery alone, 2 (1.6%) to other drug treatments, and 14 (10.9%) to no treatment. Birth weight was below the 10th percentile in 28 of 127 children (22.0%) in the prenatal-exposure group and in 19 of 125 children (15.2%) in the control group (P=0.16). There was no significant between-group difference in cognitive development on the basis of the Bayley score (P=0.08) or in subgroup analyses. The gestational age at birth was correlated with the cognitive outcome in the two study groups. Cardiologic evaluation among 47 children at 36 months of age showed normal cardiac findings. CONCLUSIONS: Prenatal exposure to maternal cancer with or without treatment did not impair the cognitive, cardiac, or general development of children in early childhood. Prematurity was correlated with a worse cognitive outcome, but this effect was independent of cancer treatment. (Funded by Research Foundation-Flanders and others; ClinicalTrials.gov number, NCT00330447.).
Keywords: novorozenec; Infant, Newborn; radioterapie; Infant, Premature; Infant; Humans; Pregnancy; zpožděný efekt prenatální expozice; Case-Control Studies; novorozenec s nízkou porodní hmotností; kojenec; kognice; studie případů a kontrol; porodní hmotnost; gestační stáří; růst; Female; Antineoplastic Agents; lidé; Growth; Radiotherapy; Infant, Low Birth Weight; předškolní dítě; vývoj dítěte; ženské pohlaví; Male; Child Development; Birth Weight; Heart; těhotenství; nádorové komplikace v těhotenství; protinádorové látky; Pregnancy Complications, Neoplastic; Prenatal Exposure Delayed Effects; mužské pohlaví; Child, Preschool; Cognition; novorozenec nedonošený; Gestational Age; srdce